FK506 prevents mitochondrial-dependent apoptotic cell death induced by 3-nitropropionic acid in rat primary cortical cultures - Almeida, Sandra (2004)
The mitochondrial toxin 3-nitropropionic acid (3-NP) has been largely used to study neurodegenerative disorders in which bioenergetic defects are implicated. In the present study, we analyzed the molecular pathways involved in FK506 neuroprotection against cell death induced by 3-NP, using cultured cortical neurons. 3-NP induced cytochrome c release and increased caspases -2, -3, -8, and -9-like activities, although, calpain activity was not significantly affected. FK506 decreased cytochrome c release and caspase-3-like activity induced by 3-NP, without changing the activities of other caspases. FK-506 also decreased the number of apoptotic neurons, determined by Hoechst. Under these conditions, FK506 alone significantly reduced calcineurin activity by about 50%. Our results also showed a decrease in mitochondrial Bax and an increase in mitochondrial Bcl-2 levels upon exposure to FK506 and 3-NP. However, no significant changes occurred in total Bcl-2 and Bax levels. Altogether, the results suggest that FK506 neuroprotection against 3-NP-induced apoptosis is associated with the redistribution of Bcl-2 and Bax in the mitochondrial membrane.